2016
DOI: 10.15353/cjds.v5i1.250
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Persons with Disabilities in Canadian Provincial Office

Abstract: This exploratory study examines the electoral experience of persons with disabilities with a particular focus on those that have sought provincial political office in Canada for the last three provincial elections in every province. It also gauges the accessibility of the environment into which they were entering when deciding to seek political office: political parties (recruitment efforts, campaign finance provisions, disability specific language in party constitutions) and the provincial electoral managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
(29 reference statements)
1
12
0
Order By: Relevance
“…As the author of this study stated, this higher voter turnout is likely due to being part of the survey which raised their consciousness on the issue and prompted them to vote (McColl, 2006). Recent work by Levesque (2016) examined the political participation of persons with disabilities in Canadian provincial office. It found that only 1.2 per cent of candidates for the last three provincial elections in each province were persons with disabilities, which is far below the rate of disability in the Canadian adult population at 16 per cent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As the author of this study stated, this higher voter turnout is likely due to being part of the survey which raised their consciousness on the issue and prompted them to vote (McColl, 2006). Recent work by Levesque (2016) examined the political participation of persons with disabilities in Canadian provincial office. It found that only 1.2 per cent of candidates for the last three provincial elections in each province were persons with disabilities, which is far below the rate of disability in the Canadian adult population at 16 per cent.…”
mentioning
confidence: 99%
“…For example, recruitment efforts, party funding mechanisms and disability provisions were lacking in political parties. Campaign finance laws were also found to be in need of revision to address the added costs persons with disabilities face when seeking elected office (Levesque, 2016; for a broader Canadian comparative comparison, see Prince, 2012b).…”
mentioning
confidence: 99%
“…However, there may be other factors, such as societal stigma, fewer resources, or a lack of role models, which can make it difficult or offputting for disabled people to become involved in political parties and seek nomination as a candidate in the first place (D' Aubin and Stienstra, 2004;Sackey, 2015;Langford and Levesque, 2017;Levesque, 2016). What is more, parties might be hesitant to recruit and select them for various reasons, including prejudice and fear of a backlash at the ballot box.…”
Section: Candidate Beliefs and Competencesmentioning
confidence: 99%
“…The rare exceptions include a recent study by Waltz and Schippers (2020) based on interviews with nine disabled politicians from four European countries and Sackey's (2015) study of disability organisations and non-disabled local government officials in Ghana. Moreover, a few studies from Canada have focused on disabled people in elected office, including Langford and Levesque's (2017) analysis of interviews with three disabled candidates and elected office holders in British Columbia; D'Aubin and Stienstra's ( 2004) discussion of disabled candidates and elected politicians; Levesque's (2016) analysis of disabled candidates in provincial elections in Canada; and Michael Prince's (2009) study of disability and the policy-making process.…”
Section: Literature Reviewmentioning
confidence: 99%